THE MAKING OF ADJECTIVE CARD GAME TO LEARN VOCABULARY FOR JUNIOR HIGH SCHOOL STUDENT’S - Fazila Uyun; Halim Dwi Putra (INOVISH JOURNAL, 2016)
Abstract : The objective of students in learning foreign language is to be able to communicate fluently. Since English is a second language in Indonesia, the effort to make students mastering this language is still seen to be difficult to do. Having rich vocabulary is the main factor supports students to speak English fluently. However, insufficient in teaching English vocabulary contributes to the inconvenient learning environment at school. Some of teachers do not have creative idea to encourage student to explore more about vocabulary. The lack of media and learning tools also contribute to those problems. The media of game for example is effective to be implemented in teaching process. The aspects of entertaining and educative are combined to convoy students to think creatively while playing. The Adjective Cards Game created to enlarge student’s ability in describing thing with their characteristics. It contains of Adjective and Noun cards with interesting pictures and information which motivate students to learn English in the class or at home with family members. Keywords: Vocabulary, Game, Adjective Card Game